Efficacy and safety of endoscopic papillectomy: a multicenter, retrospective, cohort study on 227 patients. (April 2022) - Gondran, Hannah; Musquer, Nicolas; Perez-Cuadrado-Robles, Enrique; Deprez, Pierre Henri; Buisson, François; Berger, Arthur; Cesbron-Métivier, Elodie; Wallenhorst, Timothee; David, Nicolas; Cholet, Franck; Perrot, Bastien; Quénéhervé, Lucille; et al.
Background: Endoscopic papillectomy is a minimally invasive treatment for benign tumors of the ampulla of Vater or early ampullary carcinoma. However, reported recurrence rates are significant and risk factors for recurrence are unclear. Objective: The aims of this study were to evaluate the efficacy and safety of endoscopic papillectomy and to identify risk factors for recurrence and adverse events. Methods: All patients who underwent endoscopic papillectomy at five tertiary referral centers between January 2008 and December 2018 were included. Recurrence was defined as the detection of residue on one of the follow-up endoscopies. Treatment success was defined as the absence of tumor residue on the last follow-up endoscopy. Results: A total of 227 patients were included. The resections were en bloc in 64.8% of cases. The mean lesion size was 20 mm (range: 3–80) with lateral extension in 23.3% of cases. R0 resection was achieved in 45.3% of cases. The recurrence rate was 30.6%, and 60.7% of recurrences were successfully treated with additional endoscopic treatment. Finally, treatment success was achieved in 82.8% of patients with a median follow-up time of 22.3 months. R1 resection, intraductal invasion, and tumor size > 2 cm were associated with local recurrence. Adverse events occurred in 36.6% of patients and included pancreatitis (17.6%), post-procedural hemorrhage (11.0%), perforation (5.2%), and biliary stenosis (2.6%). The mortality rate was 0.9%. Conclusion: Endoscopic papillectomy is an effective and relatively well-tolerated treatment for localized ampullary tumors. In this series, R1 resection, intraductal invasion, and lesion size > 2 cm were associated with local recurrence.